Consumers knowledge and preferences for wood-based materials used in household furniture manufacture - Mohamed, Shukri; Yaakob, Sam Shor Nahar; Y., Lilyana (Forestry Department Peninsular Malaysia, 2013)
The material a household furniture item is made of is an important attribute in consumer purchase decision making. The objective of this study was to investigate Malaysian consumers' knowledge of the common type of wood-based materials used in the manufacture of wooden household furniture, namely solid timber, plywood, particleboard and medium density fibreboard. In addition, the type of material the consumers preferred was also determined. A convenience sampling approach was adopted in recruiting the respondents for the study. Only 20% of the respondents were able to correctly identify all the four wood-based samples shown in the survey while 87% could correctly identify at least one of the samples. The consumers' material of choice is solid timber as it is considered more durable than wood panels or composites.